'I will teach you in a room, I will teach you now on Zoom … ': a contemporary expression of zooming by three practitioner/academics in the creative arts, developed through the spirit of the surrealist's exquisite corpse. Issue 3 (1st September 2020) - Pike, Shane; Neideck, Jeremy; Kelly, Kathryn
ABSTRACT: This document is a representation of how three collaborators – theatre makers and academics in the performing arts – have responded to the current experience of the 'zoom function.' Inspired by the traditions of the French-surrealists' method of collective compositional arrangement known as the 'exquisite corpse, ' Drs Pike, Neideck and Kelly have collaged a series of responses to their experience of government-mandated isolation in Queensland, Australia. An isolation punctuated by the abovementioned infiltrations of zooming, digitised bodies. The result is an expression of these infiltrations and provides an impression of how these creators have adapted, deconstructed, evolved within, and responded to this world, where it is practically impossible to "zoom out." Just as Linn Meyers [2020. "Exquisite Corpse." Art Journal 79 (1): 16–17. doi:10.1080/00043249.2020.1724030] sought to build upon the traditions of the surrealists with her graph drawing of 2012, we "exploit the [exquisite corpse] methodology as a tool for artistic collaboration" (p. 16). This non-traditional, practice-based document is a collective of three separate but intersecting contributions that are studied, shared and zoomed, from one to another and back again, successively built upon and developed, to generate a thematically linked collection of thoughts and offerings inspired, enacted and enabled by zooming.